Internal tides off the Amazon shelf in the western tropical Atlantic: analysis of SWOT Cal/Val mission data - M. Tchilibou; L. Carrere; F. Lyard; C. Ubelmann; G. Dibarboure; E. D. Zaron; B. K. Arbic (Ocean Science)
This study focuses on the internal tides (ITs) off the Amazon shelf in the tropical Atlantic. It is based on 2 km horizontally gridded observations along the swaths of SWOT (Surface Water and Ocean Topography) track 20 during the calibration/validation phase (Cal/Val, 1 d orbit) from late March to early July 2023. We evaluate the amplitude of M2, N2, and S2 frequencies and use the M2 atlas as an internal tide correction model for SWOT observations. Internal tide amplitudes (models or atlases) are first derived by harmonic analysis of the SWOT sea level anomaly (SLA). The estimation is improved by performing a principal component analysis before the harmonic analysis. The results compare very well with the high-resolution empirical tide (HRET) internal tide model, the reference product for internal tide corrections in altimetry observations. The coherent mode 1 and mode 2 M2 can be distinguished in the internal tide model derived from SWOT, while the higher modes with their strong SLA signature are seen mostly in the incoherent part. In comparison to HRET, the correction of SWOT observations with SWOT-based atlases may be more relevant for this track.